PERENCANAAN AKTIVITAS AGROWISATA DALAM MENDUKUNG PROGRAM DESA WISATA PADA DESA CUKILAN - Gunawan, Antonius; Sutrisno, Alfred Jansen (Agros Journal of Agriculture Science, 2024)
The area of land used, and the visual conditions of the agricultural landscape are required. This research aims to identify land use and activities in the agricultural sector, identify the visual conditions of the agricultural landscape, and provide recommendations for planning agricultural tourism activities. This research is qualitative research which is useful for further exploring the data needed where the research variables are visual quality and community perception, especially farmers, and combined using a quantitative approach using Scenic Beauty Estimation (SBE) data analysis to evaluate visual quality and descriptive statistics to determine farmer perceptions. Cukilan Village. The results of this research show that the agrotourism landscape planning for Cukilan Village can be implemented well and has different agricultural commodities in each planting season. The conclusion of this research is based on the results of the research, it can be concluded that the planning of agrotourism activities in Cukilan Village, especially in some villages such as Krajan 2, Salak, Patran, Banjaran Gunung, Banjaran Cengklik has different agricultural products every month. The visual quality in Cukilan Village has natural landscape visuals and gets a medium average score, which means it can give a beautiful and attractive impression to tourists.